Activation of Shikimate, Phenylpropanoid, Oxylipins, and Auxin Pathways in Pectobacterium carotovorum Elicitors-Treated Moss - Alvarez, Alfonso; Montesano, Marcos; Schmelz, Eric; Ponce de León, Inés (Frontiers in Plant Science, 2016)
Plants have developed complex defense mechanisms to cope with microbial pathogens. Pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) are perceived by pattern recognition receptors (PRRs), leading to the activation of defense. While substantial progress has been made in understanding the activation of plant defense by PAMPs and DAMPs recognition in tracheophytes, far less information exists on related processes in early divergent plants like mosses. The aim of this study was to identify genes that were induced in P. patens in response to elicitors of Pectobacterium carotovorum subsp. carotovorum, using a cDNA suppression subtractive hybridization (SSH) method. A total of 239 unigenes were identified, including genes involved in defense responses related to the shikimate, phenylpropanoid and oxylipin pathways. The expression levels of selected genes related to these pathways were analyzed using quantitative RT-PCR, confirming their rapid induction by P.c. carotovorum derived elicitors. In addition, P. patens induced cell wall reinforcement after elicitor treatment by incorporation of phenolic compounds, callose deposition, and elevated expression of Dirigent-like encoding genes. Small molecule defense markers and phytohormones such as cinnamic acid, 12-oxo-phytodienoic acid and auxin levels all increased in elicitor-treated moss tissues. In contrast, salicylic acid levels decreased while abscisic acid levels remained unchanged. P. patens reporter lines harboring an auxin-inducible promoter fused to β-glucuronidase revealed GUS activity in protonemal and gametophores tissues treated with elicitors of P.c. carotovorum, consistent with a localized activation of auxin signaling. These results indicate that P. patens activates the shikimate, phenylpropanoid, oxylipins and auxin pathways upon treatment with P.c. carotovorum derived elicitors.